2021
DOI: 10.21203/rs.3.rs-293856/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Early Corticosteroids on 60-day Mortality in Critically Ill Patients with COVID-19: A Multicenter Cohort Study of the OUTCOMEREA Network

Abstract: ObjectivesIn severe COVID-19 pneumonia, the appropriate timing and dosing of corticosteroids(CS) is not known. Patient subgroups for which CS could be more beneficial also need appraisal. The aim of this study was to assess the effect of early CS in COVID-19 pneumonia patients admitted to the ICU on the occurrence of 60-day mortality, ICU-acquired-bloodstream infections(ICU-BSI), and hospital-acquired pneumonia and ventilator-associated pneumonia(HAP-VAP).MethodsWe included patients with COVID-19 pneumonia adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
6
2
Order By: Relevance
“…It may be that prolonged and highdose courses of corticosteroids explain why our results diverge from those reported in clinical trials [39,40]. Other observational studies have found a relationship between corticosteroid use and subsequent pneumonia in single centre [42] and multi-centre cohorts [34,43], with the Dupuis and colleagues study noting a relationship between steroid dose and infection risk [34]. It is possible that steroids were prescribed because of secondary infection i.e.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…It may be that prolonged and highdose courses of corticosteroids explain why our results diverge from those reported in clinical trials [39,40]. Other observational studies have found a relationship between corticosteroid use and subsequent pneumonia in single centre [42] and multi-centre cohorts [34,43], with the Dupuis and colleagues study noting a relationship between steroid dose and infection risk [34]. It is possible that steroids were prescribed because of secondary infection i.e.…”
Section: Discussioncontrasting
confidence: 51%
“…In this study, corticosteroids were not associated with increased survival, so it is unlikely that their use increased infection due to patients surviving long enough to develop an infection in ICU. The finding of increased unadjusted mortality amongst patients receiving steroids may reflect differences between patients selected for corticosteroid therapy, although other reports have noted similar effects even after adjusting for clinical variables [33,34].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These short-term protective effects have also been found for the subgroup of patients aged < 60 years, similar findings as those observed in the RECOVERY trial which showed protective effects of corticosteroids for patients younger than 70 years. However, a multicentre study conducted in 303 critically ill COVID-19 patients found opposite results to ours, reporting that early corticosteroid administration was associated with a lower mortality rate in patients aged ≥ 60 years [40]. The contradictory results might be due to a different population than ours with only onethird of included patients under invasive mechanical ventilation.…”
Section: Discussioncontrasting
confidence: 86%
“…Other factors related to SARS-CoV-2 infection include the high frequencies of pulmonary emboli and pulmonary infarction, the particular severity and length of ARF that required prolonged mechanical ventilation (12-30 days on average [50]), deep sedation and neuromuscular blockade, and the frequent use of extracorporeal membrane oxygenation [43]. The role of steroid therapy during SARS-CoV-2 infection in the occurrence of bacterial infections is debated [51][52][53][54][55] but has been associated with systemic infections such as invasive aspergillosis [56].…”
Section: Specific Risk In Icumentioning
confidence: 99%